If a and ß are the zeroes of the quadratic
polynomial f(x) = ax? + bx + c, then evaluate:
Alpha cube + beta cube
(ii) Alpha square by beta + beta square by Alpha
Answers
Answered by
2
If alpha,beta are roots of a quadratic equation ax^2+bx+c=0,then
alpha+beta=-b/a
alpha*beta=c/a
Therefore,alpha sq.+beta sq. =(alpha+beta)^2-2.alpha.beta
=(-b/a)^2-2*c/a
=b^2/a^2-2c/a
=(b^2-2ac)/a^2
Step-by-step explanation:
Answered by
0
Answer
If alpha,beta are roots of a quadratic equation ax^2+bx+c=0,then
alpha+beta=-b/a
alpha*beta=c/a
Therefore,alpha sq.+beta sq. =(alpha+beta)^2-2.alpha.beta
=(-b/a)^2-2*c/a
=b^2/a^2-2c/a
=(b^2-2ac)/a^2
Step-by-step explanation:
Similar questions